Anemia Prevention Behaviors Based on Self-Regulation Theory Among Pregnant Women - Devi Permata Sari; Sri Sat Titi; Supardi Supardi; Istiqomah Istiqomah (Universitas Tribhuwana Tunggadewi, 2026)
Anemia in pregnant women remains a serious health problem in Indonesia, posing risks to both mothers and fetuses. Anemia prevention measures, such as taking iron tablets, maintaining a balanced diet, preventing worm infections, and attending regular antenatal care (ANC), are often suboptimal due to a lack of adherence by pregnant women. Structured and intensive interventions are needed to strengthen patient self-care behaviors through the implementation of behavioral regulation strategies, particularly self-regulation mechanisms, to support health behavior change. Self-regulation is a psychological process that enables individuals to control, direct, and evaluate their behavior to achieve specific health goals. This study aimed to examine the relationship between self-regulation and anemia prevention behavior in pregnant women at a Public Health Center in 2025. This study employed a quantitative correlational design with a cross-sectional approach. The population consisted of 130 pregnant women, with a sample of 98 women selected using accidental sampling. The research instruments were questionnaires on self-regulation and anemia prevention behavior. All questionnaire items were valid (r 0.444), and the instrument demonstrated good reliability (Cronbach's alpha = 0.87). Data analysis was conducted using the Kendall Tau test. As many as 70.4% of respondents had a high self-regulation and 61.2% had high anemia prevention behavior. Bivariate analysis yielded a p-value of 0.0001 and a correlation coefficient ? = 0.683, indicating a significant positive relationship: the stronger the self-regulation, the better the anemia prevention behavior of pregnant women. In conclusion, there is a positive relationship between self-regulation and anemia prevention behavior among pregnant women.